Implantation of ascyrus medical dissection stent, our first-hand experience - Mouhammad Kanj; Benoit Cosset; Alexandre Oliny; Fadi Farhat (Journal of Cardiothoracic Surgery, 2023)
Abstract Background Acute type A aortic dissection is associated with high perioperative morbidity and mortality. Ascyrus Medical Dissection Stent (Cryolife, Kennesaw, USA) is a novel uncovered hybrid stent graft developed to be used as an adjunct to standard surgical approach to promote true lumen expansion and enhance aortic remodeling. Methods From March 2021 to March 2022, four consecutive patients presented with acute Debakey type I aortic dissection and underwent emergent surgical repair with Tirone David procedure and implantation of Ascyrus Medical Dissection Stent. We reviewed patient’s files retrospectively and described the perioperative outcomes. Results All four device implantations were successful. Overall 30-day mortality was 0%. Malperfusion that was present in two patients pre-operatively improved after Ascyrus Medical Dissection Stent implantation. No aortic reinterventions were needed. No aortic injury related to the device was noted. Favourable changes in aortic true lumen and false lumen dimensions were found in most of our patients but the stent was compressed at the isthmus in one patient. Conclusion Ascyrus Medical Dissection Stent is a reliable and secure device. However, its benefits remain unclear when it comes to a positive remodeling and seems less likelihood comparable to a frozen elephant trunk. The main reason seems to be an insufficient radial force of the stent.